Implementasi Metode Prototype pada Pembuatan Web Portal TEFA House of Health Promotion - Veronika Vestine; Bakhtiyar Hadi Prakoso; Gandu Eko Julianto Suyoso (Jurnal Teknologi Informasi dan Multimedia, 2024)
Health Promotion is a series of activities that strive for individuals to increase their knowledge related to health so that ultimately they can improve the quality of health. In order for the objectives of health promotion activities to be achieved, media is needed to support these activities. TeFa House of Health Promotion Polije is one of the TeFa (Teaching Factories) managed by the Health Promotion study program, Department of Health. TeFa was created as a forum for communication, information and health education, TeFa is also a means for lecturers to contribute to society by providing consultation services related to the development of public health promotion programs. To support this, a multifunctional platform is needed in the form of a webportal which is used to help TeFa. This research focuses on creating a web portal using one of the SDLC methods, namely prototype. The process of creating a web portal begins with extracting information through interviews with potential users. The results of this excavation process are information related to the features of the web portal, including articles, video, audio, pooling and chat. The process of creating a Web Portal is made using the PHP programming language and Laravel Framework. The testing process is carried out using the black box method to determine the functionality of each feature. The test results showed that the web portal was in accordance with the user's required features and each feature was functioning according to its function.